The Role of Knowledge Management in Enhancing Employee Innovation and Organizational Performance: Examining the Moderating Effect of Leadership Style - Moch Agus Ramdhan (Universitas Nusa Putra, 2025)
This study explores how knowledge management can boost employee innovation and improveorganizational performance, while also examining the role of leadership style in strengthening theseconnections. The idea is that effective knowledge management can inspire employee creativity, which,in turn, enhances overall performance within the organization. Using a quantitative approach, data werecollected from employees across various organizations in Indonesia. The findings show that knowledgemanagement has a significant positive effect on both employee innovation and organizational performance.Furthermore, leadership style plays a crucial role in reinforcing the relationship between knowledgemanagement and performance. The study reveals that transformational leadership has the most powerfulimpact on improving organizational performance by fostering employee innovation. These insights arevaluable for improving human resource management practices and organizational strategies, emphasizingthe importance of adopting the right leadership style to drive sustainable innovation and performance